We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**0 **

Simplifying e * x + 2 = 0 Multiply e * x ex + 2 = 0 Reorder the terms: 2 + ex = 0 Solving 2 + ex = 0 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + ex = 0 + -2 Combine like terms: 2 + -2 = 0 0 + ex = 0 + -2 ex = 0 + -2 Combine like terms: 0 + -2 = -2 ex = -2 Divide each side by 'x'. e = -2x-1 Simplifying e = -2x-1

i think its right.

cowgirlkatie03 Sep 6, 2017